VLSI Architecture for Smart and Precision Agriculture Using Sensors - Vedulla, Tarun.; Reddy, Y. Maheswar; Kalyan, Achyuta; Jenila, R. (SOTVI, 2021)
World population has almost doubled during the last century increasing dramatically the need for food to support the population over 7 billion persons. Precision agriculture is a type of innovative agriculture, based on new technologies, which aims to streamline the agricultural process. Parameters such as temperature, humidity, soil characteristics, and nutrients all play a role in plant development. Numerous sensors are available to measure the environmental factors and depending on datum, the devices monitor and control the parameter changes for each crop. Some existing technologies are more complex and very complicated for farmers to implement. The main goal of this project is to produce precision agriculture-based grid with high performance and low energy consumption.